Association of TERT promoter mutation with oral squamous cell carcinoma: a systematic review and meta-analysis - Monal Yuwanati; Sachin Sarode; Gargi Sarode; Amol Gadbail; Shailesh Gondivkar; Akhilanand Chaurasia; Dhara Dwivedi; Sara Delgadillo-Barrera (Scientific Reports)
Abstract The telomerase reverse transcriptase (TERT) promoter mutations have been linked to the prognosis and survival of several cancers; however, it is still debatable in case of oral squamous cell carcinoma. The exact reason for it is currently unknown. However, considering its role in cell survival and proliferation it is imperative to evaluate the association between TERT promoter mutations and OSCC. The systematic review and meta-analysis were carried out to gather evidence for TERT promotor mutation in OSCC. Electronic databases along with grey literature were searched for relevant studies. We used fixed- or random-effect models to calculate pooled proportion, estimated odds ratios or standardized mean differences, and corresponding 95% confidence intervals (CIs). We included 13 eligible studies incorporating 816 cases. The average frequency of TERT promotor mutation was 46.1% (0.46, 95% CI, 0.33, 0.60). However, TERT promoter mutations were not associated with gender, habit (smoking and betel nut), nodal involvement, metastases, and TNM stage. C228T (189/287), C250T (73/287), C228A, and other variants of TERT mutation were frequently detected TERT mutation variant in OSCC. TERT promoter mutations could be considered as biomarkers assisting in risk stratification and prognostic prediction.